Classification of Kushtha According to Acharyas: A Review - Nagar, Shakuntala; Gautam, Niranjan (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is one of the most ancient systems of life, health and cure. Its antiquity goes back to the Vedas. The skin is the body’s biggest and most protective organ. A healthy skin is a reflection of good health though skin illnesses affect the body, they also cause psychological problems and can harm the affected person in a variety of ways, including discomfort, disfigurement, handicap, and death. Ayurveda has discussed all skin disease under the umbrella of Kushtha, in other word it can be listed as all Ayurvedic dermatology manifestations under 18 sub types of Kushtha. Sushruta has termed it as ‘Tvagamaya’ & it is chronic in nature.